Infeksi Nosokomial di Unit Perawatan Intensif : Pencegahan dan Pengendalian - Teguh Setiadi; Akhmad Yun Jufan; Erlangga Prasamya (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Nosocomial infections in the intensive care unit (ICU) are a significant health problem with high susceptibility rates among critically ill patients. These infections are caused by pathogenic microorganisms that spread through medical equipment, direct contact with healthcare workers, or poorly maintained environments. Key risk factors include the use of invasive devices such as catheters and ventilators, immunocompromised conditions, and inappropriate antibiotic use that can lead to antibiotic resistance. The most common types of nosocomial infections in the ICU are ventilator-associated pneumonia (VAP), central line-associated bloodstream infection (CLABSI), catheter-associated urinary tract infections (CAUTI), surgical site infections (SSI), and multidrug-resistant organism (MDRO) infections. Data shows approximately 30% of nosocomial infections occur in ICUs, with 51% of ICU patients experiencing infections and 64% of infection sources originating from the respiratory tract. Prevention and control of infections requires a comprehensive approach through implementation of prevention bundles, strict hygiene management, use of sterile medical equipment, and rational antibiotic use. Consistent infection prevention and control (IPC) programs can reduce nosocomial infection incidence, decrease morbidity, mortality, and healthcare costs in ICUs. Teguh Setiadi, Akhmad Yun Jufan, Erlangga Prasamya. Nosocomial infections in intensive care units: prevention and control.